When the son of man didn't come : a constructive proposal on the delay of the parousia - Hays, Christopher M., 1983-; Gallaher, Brandon, 1972-; Konstantinovsky, Julia; Ounsworth, Richard Joseph, 1972-; Strine, C. A. (Casey Alan), 1975- (2016)
The delay of the Parousia---the second coming of Christ---has vexed Christians since the final decades of the first century. This volume offers a critical, constructive, and interdisciplinary solution to that dilemma. The argument is grounded in Christian tradition while remaining fully engaged with the critical insights and methodological approaches of twenty-first-century scholars. The authors argue that the deferral of Christ's prophesied return follows logically from the conditional nature of ancient predictive prophecy: Jesus has not come again because God's people have not yet responded sufficiently to Christ's call for holy and godly action. God, in patient mercy, remains committed to cooperating with humans to bring about the consummation of history with Jesus' return. Collaboratively written by an interdisciplinary and ecumenical team of scholars, the argument draws on expertise in biblical studies, systematics, and historical theology to fuse critical biblical exegesis with a powerful theological paradigm that generates an apophatic and constructive Christian eschatology. The authors, however, have done more than tackle a daunting theological problem: as the group traverses issues from higher criticism through doctrine and into liturgy and ethics, they present an innovative approach for how to do Christian theology in the twenty-first-century academy. (Publisher)
Introduction: Was Jesus wrong about the eschaton? / Christopher M. Hays -- Prophecy : a history of failure? / Christopher M. Hays -- Reconceiving prophecy : activation, not prognostication / C.A. Strine -- The delay of the parousia : a traditional and historical-critical reading of scripture: part 1 / Christopher M. Hays, Richard J. Ounsworth OP -- The delay of the parousia : a traditional and historical-critical reading of scripture: part 2 / Christopher M. Hays -- Negating the Fall and re-constituting creation : an apophatic account of the redemption of time and history in Christ / Julia S. Konstantinovsky -- Divine possibilities : the condescension of God and the restriction of divine freedom / Brandon Gallaher, Julia S. Konstantinovsky -- Divine action in Christ : the Christocentric and Trinitarian nature of human cooperation with God / Brandon Gallaher, Julia S. Konstantinovsky -- Liturgy : partial fulfillments and the sustaining of God's people / C.A. Strine, Richard J. Ounsworth OP, Brandon Gallaher -- Our method : reflections on our hermeneutical principles and collaborative practices / Christopher M. Hays, C.A. Strine -- Conclusion: A fourfold response to the delay of the parousia / Christopher M. Hays.
"This volume represents four years of collaborative work by the Oxford Postdoctoral Colloquium on Eschatology."--Acknowledgments, page xi.
Includes bibliographical references (pages 269-289) and indexes.
Keywords: Eschatology; Apophatic theology